Mulighederne for udviklingen af en fungibel tværkulturel psykologi - Berliner, Peter (Psyke & Logos, 2023)
To make modern psychology more useful to people in developmental countries or in different subcultural and etnich groups, it is necessary to evolve a cross-cultural psychology on the basis of systematical interventions in changes (i.e. developmental processes) in those groups in question. In this article theoretical and methodical prerequisites for such a model are considered. The basis of the model is intervention. Thus the model is a mean of conceptualizing specific situational and contextual conditions and processes. Further more the model focus on ressources of actual and future development. The complexity of the context demands a model consisting of a multiple of theoretical approaches. The topic of the model are changes in society, on the group level and on the individual level. Changes mean alterations of particularly elements (i.e. processes) of interpersonel interaction - for instance specific parts of sign systems, of activity concerning labour or other social practices, specific institutionalized forms of communication (schools, trade, political debate etc.). The model, i.e. this sort of psychological interventionsindifferent cultural contexts, is used on material concerning the cognitive style of children in small Greenlandic settlements. It is shown how cognition in faet is the way, the children use their cognitive skills in interpersonel interactions. Tue essential point is how the children cope with demands from teachers and parents. Using the model on a case concerning a young Greenlandic man, it is shown that no simple connection is to be found between personal symptoms and biculturalism. The symptoms may of different courses incorporate biculturalism - and then on the conscious level falsely perceive biculturalism as the main course of the problems. The aim ofthe articel is to evolve a usable cross-cultural psychology- and thus overcome and integrate the criticism concerning the current cross-cultural psychology in the above outlined model of systematical interventions in changes.